Identification of potent chromone embedded [1,2,3]-triazoles as novel anti-tubercular agents - Nalla, Viswanadh; Shaikh, Aslam; Bapat, Sanket; Vyas, Renu; Karthikeyan, M.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, M. (Royal Society Open Science, 2018)
A series of 20 novel chromone embedded [1,2,3]-triazoles derivatives were synthesized via an easy and convenient synthetic procedure starting from 2-hydroxy acetophenone. The in vitro anti-mycobacterial evaluation studies carried out in this work reveal that seven compounds exhibit significant inhibition against Mycobacterium tuberculosis H37Rv strain with MIC in the range of 1.56-12.5 mu g ml(-1). Noticeably, compound 6s was the most potent compound in vitro with a MIC value of 1.56 mu g ml(-1). Molecular docking and chemoinformatics studies revealed that compound 6s displayed drug-like properties against the enoyl-acyl carrier protein reductase of M. tuberculosis further establishing its potential as a potent inhibitor.